Respuesta :

Answer: C=4

Step-by-step explanation:

5(5c-1)-1 = 23c + 6

1. Using PEMDAS. You know to do parenthesis first which is 5(5c-1)

Using distributive property you will get 25c-1-1 = 23c + 6

2. Simply on both sides and get 25c-2=23c+6

3. Using the rule that whatever you do on one side of the equal sign, you do on the other you can subtract 23c from both sides and get 2c-2=6. Then add 2 on both sides and get 2c=8

4. Divide both sides by 2 to get rid of the 2 and you get c=4

Solution for 5(5c-1)-1=23c+4 equation:

Simplifying
5(5c + -1) + -1 = 23c + 4

Reorder the terms:
5(-1 + 5c) + -1 = 23c + 4
(-1 * 5 + 5c * 5) + -1 = 23c + 4
(-5 + 25c) + -1 = 23c + 4

Reorder the terms:
-5 + -1 + 25c = 23c + 4

Combine like terms: -5 + -1 = -6
-6 + 25c = 23c + 4

Reorder the terms:
-6 + 25c = 4 + 23c

Solving
-6 + 25c = 4 + 23c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-23c' to each side of the equation.
-6 + 25c + -23c = 4 + 23c + -23c

Combine like terms: 25c + -23c = 2c
-6 + 2c = 4 + 23c + -23c

Combine like terms: 23c + -23c = 0
-6 + 2c = 4 + 0
-6 + 2c = 4

Add '6' to each side of the equation.
-6 + 6 + 2c = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 2c = 4 + 6
2c = 4 + 6

Combine like terms: 4 + 6 = 10
2c = 10

Divide each side by '2'.
c = 5

Simplifying
c = 5